EFFICACY AND SAFETY OF CONTROLLED RELEASE METOPROLOL TARTRATE IN PATIENTS WITH ARTERIAL HYPERTENSION: ERA STUDY RESULTS - O. L. Barbarash; M. V. Zykov (Столичная издательская компания, 2016)
Aim. To evaluate efficacy, safety and influence on quality of life of controlled release metoprolol tartrate (CRMT) in patients with arterial hypertension of 1-3 degree.Material and methods. 603 patients (256 men and 347 women; 60,1 y.o., in average) with hypertension of 1-3 degree were examined. 67 hypertensive patients had diabetes mellitus (DM). Study duration was 2 months. All patients started monotherapy by CRMT 50-100 mg OD. After 15 days of CRMT therapy daily dose could be increase to 100-150 mg, if the target blood pressure (BP) levels were not reached. After 1 month of treatment if necessary CRMT daily dose could be increased again up to 150-200 mg or another antihypertensive drug could be added. The forth visit after 2 month of therapy was last one. Antihypertensive efficacy, safety and quality of life (by visual analogue scale) were assessed at every visit. Besides the main blood biochemical parameters and electrocardiograms were analyzed for the safety control.Results. 591 patients completed the study, 12 patients dropped out the study (because of side effects or low treatment compliance). After 2 months of therapy systolic and diastоlic BP was reduced by 36 and 17 mmHg respectively (р<0,001 for both), and target BP levels was achieved in 72,9% and in 78,2% of patients respectively (р<0,01 for both). Target systolic BP (<130 mmHg) and diastolic BP (<80 mmHg) levels were achieved in 27,3% and 28,8% of hypertensive patients with DM, respectively (р<0,01 for both).Side effects were observed in 3,2% of patients. 87% of patients considered therapy tolerability as a good one. CRMT therapy resulted in quality of life rise from 55,7 to 75,4 points (р<0,001) by the end of therapy.Conclusion. Study results show high efficacy and safety of CRMT in the therapy of hypertensive patients including hypertensive patients with DM.